Combined Processing of Facial and Vocal Emotion in Remitted Patients With Bipolar I Disorder. (7th February 2019) - Hoertnagl, Christine M.; Biedermann, Falko; Yalcin-Siedentopf, Nursen; Welte, Anna-Sophia; Frajo-Apor, Beatrice; Deisenhammer, Eberhard A.; Hausmann, Armand; Kemmler, Georg; Muehlbacher, Moritz; Hofer, Alex
Abstract: Objectives: Bipolar disorder (BD) is associated with impairments in facial emotion and emotional prosody perception during both mood episodes and periods of remission. To expand on previous research, the current study investigated cross-modal emotion perception, that is, matching of facial emotion and emotional prosody in remitted BD patients.Methods: Fifty-nine outpatients with BD and 45 healthy volunteers were included into a cross-sectional study. Cross-modal emotion perception was investigated by using two subtests out of the Comprehensive Affective Testing System (CATS).Results: Compared to control subjects patients were impaired in matching sad ( p < .001) and angry emotional prosody ( p = .034) to one of five emotional faces exhibiting the corresponding emotion and significantly more frequently matched sad emotional prosody to happy faces ( p < .001) and angry emotional prosody to neutral faces ( p = .017). In addition, patients were impaired in matching neutral emotional faces to the emotional prosody of one of three sentences ( p = .006) and significantly more often matched neutral faces to sad emotional prosody ( p = .014).Conclusions: These findings demonstrate that, even during periods of symptomatic remission, patients suffering from BD are impaired in matching facial emotion and emotional prosody. As this type of emotion processing is relevant in everyday life, our results point to the necessity to provide specific training programs to improve psychosocial outcomes. ( JINS, 2019, 25, 336–342)